Exhaustive exploration of the conformational landscape of mono- and disubstituted fivemembered rings by DFT and MP2 calculations - Stortz, Carlos A. (2019)
Fil: Fil: Stortz, Carlos A. Universidad de Buenos Aires. Facultad de Ciencias Exactas. Departamento de Química Orgánica. Centro de Investigaciones en Hidratos de Carbono (CIHIDECAR); Argentina.